Role of Nanotechnology in Cancer Treatment - Sanjay R.Kumavat, (AG Volumes, 2025)
One rapidly developing cutting-edge area with several uses in novel cancer detection platforms is nanotechnology. Nanoparticles are being used to enhance the identification and treatment of a number of disorders, including cancer. Nanotechnology has enabled the use of nanoparticles in cancer therapy, which are capable of passively aggregating at tumour sites, rendering them an ideal alternative to conventional methods. This article reviews studies on the use of nanotechnology to cancer therapy from a variety of sources. From the review it concluded that nanotechnology plays a crucial role in revolutionizing cancer treatment by enhancing diagnosis, drug delivery, and therapy. Nanomedicine offers high sensitivity, specificity, and improved pharmacokinetics, enabling targeted drug delivery with reduced toxicity and enhanced therapeutic efficacy. Various nanoparticles, including polymeric, metallic, and hybrid NPs, provide platforms for combination therapy, overcoming multidrug resistance. Despite challenges in specificity, biodistribution, and clinical efficacy, ongoing research is optimizing “nanoparticle-based drug delivery”. Diagnosis and therapy integration (theragnosis) exhibits significant potential for personalised cancer treatment. With continuous advancements, nanotechnology is transforming oncology, offering innovative solutions for efficient, site-specific, and cost-effective cancer management.